PROFESIONALISASI PENGAWAS PENDIDIKAN DALAM KONTEKS OTONOMI DAERAH - Surya, Priadi (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
Educational supervisor is a professional position that is intended to provide professional development. It is supporting the principals, teachers, and school institutions. Supervisor provides the supervision of academic, administrative and managerial to the education unit. Supervisor must have the competencies of personality, managerial supervision, supervision of academic, evaluation of education, research and development and social competence. Regional autonomy provides flexibility of creation in school management. Supervisor is assisting the school principal and teachers to develop educational programs that based on their self-environment as well as potential insight of the institution into the international relations. The main model which proposed by the ministry of education in the context of regional autonomy is the School Based Management (SBM) and the implementation of the Education Unit Level Curriculum (EULC).